The EMU after three years: Lessons and challenges - Peter Bofinger (University of Würzburg, Department of Economics, 2002)
The first three years of European Monetary Union provide a good basis for a comprehensive analysis of this unprecedented and controversial monetary arrangement. The paper starts with a short discussion of the recent changeover to Euro notes and coins and the general difficulties with the European Central Bank was confronted during the last three years. It then analyses the performance of the common monetary policy in terms of price stability and real growth and in terms of the important task of establishing credibility for the new institution. It discusses the role of the ECB's two pillar strategy and presents an alternative framework for the analysis of the ECB's interest rate policy. As the weak Euro has received much public attention, the paper tries to shed some light on the most important explanations that were put forward especially in 1999 and 2000 and offers an additional argument based on the theory of behavioural finance. As the aggregate monetary policy does not necessarily fit to all individual member countries, the paper analyses whether national fiscal policies have been able and willing to counteract an inadequate monetary policy stance. It also tries to identify to what extend national inflation rates were influenced by the Balassa-Samuelson effect. In the last part the paper deals with some aspects of the eastern enlargement, above all the problems that could by associated with a lack of real convergence.
Keywords: E50; E52; E58; 330; European Central Bank; monetary policy